Analisis Penggunaan Game Based Learning Terhadap Minat Belajar Peserta Didik pada Mata Pelajaran IPS di Sekolah Dasar - Alya Nazwa Minisa; Falmoza Tsabita; Adrias Adrias; Salmaini Putri Syam (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2025)
This study aims to analyze the use of the Game-Based Learning (GBL) method in enhancing students' learning interest in Social Studies at the elementary school level. The research employs the Systematic Literature Review (SLR) method by examining various relevant previous studies. The findings indicate that the implementation of GBL significantly increases student engagement, conceptual understanding, and learning motivation. Various game-based learning models, both those utilizing technology and interactive media, have been proven to create a more engaging and effective learning environment compared to conventional methods.